Plasma xanthine oxidoreductase is associated with carotid atherosclerosis in stable kidney transplant recipients. Issue 4 (14th October 2021) - Oki, Rikako; Hamasaki, Yoshifumi; Komaru, Yohei; Miyamoto, Yoshihisa; Matsuura, Ryo; Akari, Seigo; Nakamura, Takashi; Murase, Takayo; Doi, Kent; Nangaku, Masaomi
Abstract: Aim: Xanthine oxidoreductase (XOR) is known as an enzyme related to purine metabolism, catalysing the oxidation of hypoxanthine to xanthine and of xanthine to uric acid. We investigated the relationship between plasma XOR activity in stable kidney transplantation (KT) recipients and carotid artery lesions. Methods: A total of 42 KT patients visiting our outpatient clinic on regular basis were recruited. Associations between plasma XOR activity and the existence of plaque in the common carotid artery (CCA) or internal carotid artery (ICA) and maximum intima‐medial thickness (IMT) of CCA (max‐CIMT) > 0.9 mm were examined using univariate and multivariate analyses. Results: At blood sampling, the mean and SD patient age was 52.7 ± 13.8 years old. Plasma XOR(pmol/h/ml) activity was significantly higher in patients with CCA/ICA plaque or max‐CIMT >0.9 mm than those without. [23.9 (11.8, 38.3) vs. 8.29 (6.67, 17.5), p  < .01, 23.9 (16.9, 71.2) vs. 9.16 (6.67, 28.2), p  = .01] Univariate and multivariate logistic regression analyses revealed age and plasma XOR activity as independent predictors of CCA/ICA plaque or max‐CIMT >0.9 mm. Receiver operator characteristic curve analyses revealed that the cutoff value of plasma XOR activity for the diagnosis of CCA/ICA plaque or CCA‐IMT > 0.9 mm was 16.3 pmol/h/ml. Conclusion: Plasma XOR activity is associated independently with atherosclerotic changes in the carotid artery of stable post‐KT patients. SUMMARY AT A GLANCE: Among 42 stable kidney transplant recipients, plasma xanthine oxidoreductase activity is independently associated with atherosclerotic changes as reflected by carotid intimal thickness and plaque size.